E-RESOURCES SEBAGAI PENYEDIA INFORMASI MURAH DAN BERKUALITAS (STUDI KASUS PERPUSTAKAAN NASIONAL REPUBLIK INDONESIA) - Lisa Noviani Maghfiroh (Jurnal Pustaka Ilmiah, 2019)
This paper aims to explain e-resources as a provider of information in the National Library of the Republic of Indonesia. In this paper using qualitative research methods descriptive case study approach in the National Library of the Republic of Indonesia with data collection methods through literature review. The result of the discussion is to know the role of e-resources as a provider of quality information and guidelines for accessing e-resources owned PNRI provided for the wider community so that the public and users of National Library of the Republic of Indonesia can obtain the informationneeded cheap and cheap.Keywords : E-resources, Information, National Library of the Republic of Indonesia, PNRI